Crosslinking assisted fabrication of ultrafine poly(vinyl alcohol)/functionalized graphene electrospun nanofibers for crystal violet adsorption. Issue 22 (14th February 2018) - Chailek, Nirumon; Daranarong, Donraporn; Punyodom, Winita; Molloy, Robert; Worajittiphon, Patnarin
ABSTRACT: This article reports the fabrication of water‐stable electrospun mats made from water‐soluble poly(vinyl alcohol) and comprising ultrafine nanofibers for a high surface area to volume ratio as required for the adsorption of crystal violet. Acid‐catalyzed crosslinking is uniquely demonstrated as a facile strategy to improve water stability and, just as importantly, fine‐tune the nanofiber size of the electrospun mats. Amine‐functionalized graphene nanoplatelets are incorporated as an adsorption performance enhancer instead of the more widely reported graphene oxide. The functionalized graphene also facilitates fabrication of the composite electrospun mats by direct mixing of the water‐dispersible graphene with the aqueous polymer solution. The enhanced adsorption performance of the polymer nanocomposite mats is explained in detail at the molecular level, while the adsorption mechanism is supported by adsorption isotherm and related kinetic data. Moreover, the adsorbent mats can be removed from the water after use with the mat integrity still maintained. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46318. Abstract :